2012
DOI: 10.2169/internalmedicine.51.7442
|View full text |Cite
|
Sign up to set email alerts
|

A Survival Case of Cardiogenic Shock due to Left Main Coronary Artery Myocardial Infarction: Successful Cooperation with On-Site Percutaneous Coronary Intervention and Helicopter Emergency Medical Service

Abstract: A 54-year-old man was referred to a local hospital, located about 90 km from our hospital, with cardiogenic shock due to left main coronary artery infarction (LMCA-MI). Percutaneous coronary intervention (PCI) was performed under intra-aortic balloon pumping (IABP) support, but resulted in insufficient reperfusion and his condition worsened. The helicopter emergency medical service (HEMS) rapidly transported the patient to our hospital. After percutaneous cardio-pulmonary support system (PCPS) insertion, PCI c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…More and more evidence, including the results from our study, has demonstrated that IABP insertion is associated with a higher incidence of severe bleeding and stroke. Four risk factors for complications following IABP insertion were identified from the Benchmark Registry: 51 age ≥75 years, female sex, peripheral arterial disease, and body surface area <1.65 m 2 . In the meta-analysis published by Sjauw et al, 13 a significantly increased rate of stroke secondary to IABP use was observed in patients suffering from AMI.…”
Section: Discussionmentioning
confidence: 99%
“…More and more evidence, including the results from our study, has demonstrated that IABP insertion is associated with a higher incidence of severe bleeding and stroke. Four risk factors for complications following IABP insertion were identified from the Benchmark Registry: 51 age ≥75 years, female sex, peripheral arterial disease, and body surface area <1.65 m 2 . In the meta-analysis published by Sjauw et al, 13 a significantly increased rate of stroke secondary to IABP use was observed in patients suffering from AMI.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of counterpulsation hemodynamic effect depends on several factors including the relation of balloon volume to aorta size, heart rate and rhythm and aortic compliance [17]. In addition, diastolic augmentation is most efficient the closer the balloon is to the aortic valve [18]. To minimize the risk of cerebral embolism, the ideal IABP position in modern practice is 1 or 2 cm distal to the origin of the left subclavian artery.…”
Section: Pathophysiology and Effects Of Aortic Counterpulsation On Systmentioning
confidence: 99%
“…However, the data suggest that the degree of coronary artery stenosis and the state of coronary autoregulation causes significant variation in response to counterpulsation. Kimura et al [18], using an anesthetized canine model, showed that diastolic forward flow in the left anterior descending artery increased by 12% during counterpulsation. However, with partial ligation of the left main to create a critical stenosis, the effect of counterpulsation to augment left anterior descending artery flow was completely abolished [18].…”
Section: Pathophysiology and Effects Of Aortic Counterpulsation On Systmentioning
confidence: 99%
See 2 more Smart Citations